Acute Poisoning Types and Prevalence in Shanghai, China, from January 2010 to August 20111. Issue 2 (6th December 2013) - Zhang, Jingshuo; Xiang, Ping; Zhuo, Xianyi; Shen, Min
Abstract In recent years, the number of cases of acute poisoning has increased in China, yet; currently, there is no detailed report published that addresses acute poisoning in the mainland of China. We collected biological samples from 466 cases of suspected acute poisoning at the hospitals in Shanghai, China, and examined them using spectroscopy, chromatography and chromatography/mass spectrometry. Of the 466 cases, 230 cases (100 men and 130 women) were positively confirmed as acute poisonings. There were 80 types of compounds identified in this study. Medications were the most frequent substances identified, and the other substances included pesticides, multiple compounds, volatile compounds, natural toxins, and others. The results of this study indicate a need for strengthening the education about and management of the rational and safe use of drugs in Shanghai.